Bedlis Mirliği Hâkimiyetinde Muş - Kıran, Abdullah (Muş Alparslan Üniversitesi, 2020)
Şeref Han, Şerefname (Kürd Tarihi) adlı eserinde, Muş’un da bağlı olduğu Bedlis Mirliği’nin kuruluş tarihini Sasani İmparatorluğu dönemine kadar götürür. Şeref Han’a göre, Bedlis Mirliğinin tarihi, eseri Şerefname’yi kaleme aldığı 1597 yılından, 760 yıl geriye gitmektedir. Şeref Han, 760 yıllık hükümdarlık süresinde, Bedlis Beylerinin yönetiminde 110 yıl kadar kesinti yaşandığını belirtir. Ancak buna rağmen, on sekiz Bedlis hükümdarının ülkeyi yönetme süresinin 450 yıldan fazla olduğunu yazar. Kuşkusuz Bedlis Mirliği, 19. yüzyılın ilk çeyreğine dek varlığını devam ettirmiştir. Yaklaşık 1000 yıllık bir geçmişi olan Bedlis Mirliği, muhtemelen dünyada, aynı hanedanlığın en uzun süre ile yönettiği hükümetler arasında yer alır. Bedlis hükümdarının adına sikke kesilir ve hutbede adları okunur. Bedlis Mirliği idari, siyasi ve askeri yapılanmasıyla, vakıfları ve eğitim sistemiyle bir devlet teşkilatlanmasıydı.

In his work titled Sherefname (History of Kurdish), Sherf Han takes the founding date of Bedlis Principality, to which Mush is also a part, back to the period of the Sassanid Empire. According to Sheref Han, the history of the Bedlis Principality goes back 760 years from the year 1597, when he wrote the Sherefname. Sheref Han states that during this 760-year reign, there was a 110-year interruption in the administration of Bedlis Beys. However, despite this, it is written that 18 Bedlis rulers ruled the country for more than 450 years without interruption. Undoubtedly, Bedlis Principality continued its existence until the first quarter of the 19th century. Bedlis Principality, which has a history of about 1000 years, is probably among the governments of the same dynasty for the longest time in the world. Coin (many) was printed in the name of the Bedlis ruler and their names are read in the religious sermons. Bedlis Principality was a state organization with its administrative, political and military structure, foundations and education system.
Muş Under the Sovereignty of the Bedlis Principality
anemon
Keywords: Muş; Kürt Beylikleri; Bedlis Beyliği; Şeref Hanlar; Yönetim; Muş; Kurdish principalities; Bedlis principality; Sheref Han’s Dynasty; Administration